Pengaruh Penggunaan Media Pembelajaran Compact Disk Interaktif Terhadap Motivasi Belajar Matematika Kelas V Sekolah Dasar - Mai Sri Lena; Hana Shilfia Iraqi; Wikimalzis Wikimalzis; Rahman Walid Habibi (BADAN PENERBIT STIEPARI PRESS, 2023)
Students in elementary schools are asked to study mathematics. Mathematics is a basic subject and also a means of scientific thinking, students are encouraged to study material that can be understood and used in everyday life. Besides students carrying out the teaching and learning process in class, students should have a strong motivation to carry out learning. In order for this motivation to continue to increase, educators must be active, creative, and innovative in designing student learning processes, using learning media that attract students and create joyful learning conditions. The purpose of this research is to determine the effect of interactive CD-ROM learning media on students' motivation to learn mathematics V SDS TRISULA PERWARI. In this study, the researcher used a qualitative descriptive research method with the research subject being fifth grade students at SDS TRISULA PERWARI.